2018
DOI: 10.1007/s00467-018-4136-7
|View full text |Cite
|
Sign up to set email alerts
|

Central systolic blood pressure and central pulse pressure predict left ventricular hypertrophy in hypertensive children

Abstract: Background Central systolic and pulse pressures are stronger predictors of cardiovascular risk and hypertensive organ damage than brachial blood pressure. It is suggested that isolated systolic hypertension typically seen in adolescents is associated with normal central blood pressure and does not lead to organ damage and this phenomenon is called spurious hypertension. Methods We assessed the prevalence of spurious hypertension and analyzed utility of pulse wave analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 38 publications
(48 reference statements)
5
42
1
1
Order By: Relevance
“…Because of the low number of subjects in each group, we did not find any statistically significant differences in sex distribution between those who maintained or normalized their BP status and those who increased cSBP, but numerically there were more females in the group which increased cSBP (9 vs. 30%, respectively). The 3 times higher percentage of females in the group which increased cSBP is in agreement with both our previous study (24.4%) and the overall sex distribution among adolescents with PH [9].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Because of the low number of subjects in each group, we did not find any statistically significant differences in sex distribution between those who maintained or normalized their BP status and those who increased cSBP, but numerically there were more females in the group which increased cSBP (9 vs. 30%, respectively). The 3 times higher percentage of females in the group which increased cSBP is in agreement with both our previous study (24.4%) and the overall sex distribution among adolescents with PH [9].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to our previous studies we did not find any changes in BMI or WC, both expressed in absolute and standardized values, as predictors of cSBP change. However, it must be underlined that subjects from this study had relatively normal BMI and WC values which were close to the median of the population norm (BMI-SDS and WC-SDS both below 1.0) and had lower BMI and WC than patients with ISH and elevated cSBP, as reported previously [9].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, we found LVM and LVMI were both higher in hypertension children, and among 44 hypertension adolescents, 11.36% (5/44) of them had LVH. Similar, Litwin et al demonstrated 10.3% of 44 hypertension children had some form of LV hypertrophy in the USA population [25], and Falkner reported among 35 African-American adolescents, 19% of them had LV hypertrophy [26]. Also, a cross-sectional study of 101 primary hypertension children reported that 34% of them had LV hypertrophy [27].…”
Section: Discussionmentioning
confidence: 61%
“…Оценка САД ао производилась путем построения кривой усредненной формы пульсации в восходящей аорте на основании кривой изменения давления в плечевой артерии с помощью прямого и обратного преобразования Фурье и передаточной функции, разработанной O'Rourke и соавторами на основании сопоставления прямого инвазивного измерения АД в аорте и плечевой артерии, а также с помощью заложенных в программе Vasotens математических алгоритмов [14]. В настоящее время не вызывает сомнения, что величина центрального АД лучше коррелирует с выраженностью гипертрофии левого желудочка (ГЛЖ) и сердечно-сосудистыми исходами [7,15,16]. В связи с чем ее определение является предпочтительным при ведении гипертензивных пациентов.…”
Section: материал и методыunclassified